Second generation tyrosine kinase inhibitor therapy associated with significant carotid stenosis onset: A clinical case report and literature review. - Bramucci, Alberto; Peretti, Elisa; Corsetti, Maria Teresa; Colò, Gabriele; Guagliano, Alberto (Acta Biomedica Atenei Parmensis, 2024)
Introduction: Tyrosine kinase inhibitors (TKI) are employed in the treatment of chronic myeloid leukemia (CML). Concerns about cardiovascular side effects have evolved, especially in patients with cardiovascular risk factors. Recommendations published in 2020 stress the need for preventative, biannual peripheral arterial evaluations, but there is no mention of carotid artery surveillance. We describe significant carotid artery stenosis onset in a young patient with CML treated with TKI therapy, without baseline cardiovascular risk factors. Case: A 55-year-old man was diagnosed with CML in 2016 and was prescribed Nilotinib 300 mg twice daily. Anamnesis reported identified a positive family history for cardiovascular disease only. Supra-aortic vessels Doppler ultrasound (DUS) in 2021 confirmed insignificant left internal carotid artery (ICA) stenosis, which increased to ICA stenosis with hemodynamic consequences, observed in 2023. A computed tomography angiography (CTA) confirmed stenotic progression, estimated between 80-85% over a 2-year period. A multidisciplinary team suggested revascularization with carotid endarterectomy (CEA) performed under general anesthesia with instrumental cerebral intraoperative monitoring. The patient had an uneventful post-procedural course and was discharged post-operative day 2. Post-operative 30-day DUS confirmed ongoing technical success.Conclusion: Our case report emphasizes the need for clinician awareness of a potential risk of carotid artery disease onset in patients undergoing Nilotinib therapy, independently of age and baseline cardiovascular risk factors.